Comparison of Apically Extruded Debris Associated with Different Irrigation Techniques after Removal of Intracanal Medicaments - El-Din, Shaimaa Nasr; Ali, Magdy M.; Hassan, Reham (Open Access Macedonian Journal of Medical Sciences, 2021)
This study aimed to compare the effect of XP-endo Finisher file (XPF), passive ultrasonic irrigation (PUI) and conventional irrigation technique using side-vented needle (SVN) on the amount of apically extruded debris after the removal of calcium hydroxide Ca(OH)2 and double antibiotic paste (DAP). Materials and Methods: Sixty extracted human mandibular premolars were used. After decronation, all canals were prepared up to the ProTaper Next X4 file (Dentsply Maillefer, Ballaigues, Switzerland). After dryness, teeth were randomly assigned into 2 groups (n=30) according to the Type of intracanal medication used; Ca(OH)2 and DAP then incubated at 37 °C and 100% humidity. After one week, Samples in each group were randomly assigned to 3 subgroups (n=10) according to the method used for medicament removal: XPF, PUI and SVN. Debris extruded during the removal procedure were collected into pre-weighed Eppendorf tubes then left to dry in an incubator at 37°C for 15 days. The amount of extruded debris was assessed with an analytical balance and calculated by subtracting the initial weight from the final weight of the tube. Data were statistically analyzed using Kruskal-Wallis and Mann-Whitney U test. Results: there was no statistically significant difference regarding the amount of apically extruded debris after using the three irrigation techniques in removal of both Ca(OH)2 and DAP (P-value = 0.141, Effect size = 0.160) and (P-value = 0.237, Effect size = 0.073) respectively. Conclusions: Neither XPF nor PUI increase the risk of intracanal medicament extrusion beyond the apex.